Validation of the English version of the quality of life questionnaire of the European Foundation for Osteoporosis (QUALEFFO) in Malaysia - Lai, P.S.M.; Chua, S.S.; Chan, S.P.; Low, W.Y. (2008)
Background: Osteoporotic fractures will soon become a common problem in Asian Countries including Malaysia, as the growth in the elderly population will be more marked in this region. This leads to loss of independence and reduced quality of life (QOL). QOL is used as an outcome measure in clinical trials to focus the management of diseases on the patient rather than the disease, To date, no such instrument for measuring QOL of osteoporosis patients has been validated in Malaysia. Aim: To investigate the reliability and validity of the English version of the Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO) in Malaysia. Methods: QUALEFFO was administered twice to postmenopausal osteoporotic women on alendronate. The patient group consisted of 46 women with back pain while the control group consisted of 42 women without back pain. Results: High internal consistency was seen in all domains in the QUALEFFO with Cronbach alpha of 0.74-0.95 and 0.53-0.89 in the patient and control group, respectively. Factor analysis also showed that each domain consisted of one component except for the social domain. The test-retest reliability showed high correlation coefficient in all domains (0.50-0.90, P < 0.001). Patients with back pain showed significantly worse QOL in the overall total QUALEFFO score compared to the control group (P < 0.0001). Conclusions: The English version of QUALEFFO was found to be reliable and valid for the evaluation of patients with osteoporosis and who understand English in Malaysia. This Study also indicates that patients with back pain have poorer QOL.